Diseño y modelación de un prototipo de un recuperador de energía para unidades médicas en el sistema de climatización - Carabalí Encarnación, Henry Leandro (Universidad Antonio Nariño, 2022)
The main objective of this work is to develop an energy saver for medical units that renew all their air conditioning. The motivation for the development of this project is based on the need to propose an energy recovery unit that reduces the consumption generated by medical units that renew all their air conditioning, since this type of medical unit demands many tons cooling for its operation in the air conditioning system of a clinic or hospital. To achieve the energy recovery design, a new psychrometric process was proposed based on a mixing chamber type exchanger, which will carry out energy recovery. A sketch of this energy recuperator will also be designed and presented in 3D.